2004
DOI: 10.1063/1.1831563
|View full text |Cite
|
Sign up to set email alerts
|

Growth and morphology of 0.80eV photoemitting indium nitride nanowires

Abstract: InN nanowires with high efficiency photoluminescence emission at 0.80 eV are reported for the first time. InN nanowires were synthesized via a vapor solid growth mechanism from high purity indium metal and ammonia. The products consist of only hexagonal wurtzite phase InN. Scanning electron microscopy showed wires with diameters of 50-100nm and having fairly smooth morphologies. High-resolution transmission electron microscopy revealed high quality, single crystal InN nanowires which grew in the <0001> directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(78 citation statements)
references
References 25 publications
5
72
1
Order By: Relevance
“…For InN:Si nanowires, the Si cell temperatures were ∼ 1250 • C and ∼ 1350 • C, respectively. Compared to the previous approaches in growing InN nanowires, 8,21,32,36,[47][48][49][50][51] in this experiment an In seeding layer (∼ 0.6 nm) was first deposited in situ onto Si (111) surface prior to the growth initiation, which can promote the formation and nucleation of InN nanowires. The detailed growth procedures were described elsewhere.…”
Section: Experimental Setupsmentioning
confidence: 99%
See 1 more Smart Citation
“…For InN:Si nanowires, the Si cell temperatures were ∼ 1250 • C and ∼ 1350 • C, respectively. Compared to the previous approaches in growing InN nanowires, 8,21,32,36,[47][48][49][50][51] in this experiment an In seeding layer (∼ 0.6 nm) was first deposited in situ onto Si (111) surface prior to the growth initiation, which can promote the formation and nucleation of InN nanowires. The detailed growth procedures were described elsewhere.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN. 20,23,27,29,30,[37][38][39] The electron accumulation at polar InN surface has been explained by the presence of large density of the occupied In-In bond states above the conduction band minimum (CBM), 23 as well as the unusual positioning of the branch point energy (E B ) well above the CBM at the Γ-point, which allows donor-type surface states to exist in the conduction band; 20 for polar InN surface, theoretical studies agree well with experiments.…”
mentioning
confidence: 99%
“…In recent years, research interest has been directed towards studying InN nanowires (NWs) which exhibit many fascinating properties of InN thin films. Although several studies on InN NW synthesis [9], photoluminescence [10], electroluminescence [11], metal contacts [12], field effect transistors (FETs) [13] and THz emission [14] have been reported, many interesting properties of InN NWs have not yet been adequately understood. Slow progress in research on InN NWs can be attributed partly to synthesis issues such as low growth rate (only a few microns per hour) and poor material quality [15][16][17][18].…”
mentioning
confidence: 99%
“…Growth mechanism of InN nanostructures from In 2 O 3 powder is explained based on the VS mechanism. Earlier reports could not provide an appreciable explanation for the temperature dependent evolution of morphology in InN nanostructures [13,15]. We correlate the evolution of morphology with the nucleation rate and growth rates of newly grown phase during the conversion of In 2 O 3 to InN at a given temperature.…”
Section: Growth Mechanism Of Nanorodsmentioning
confidence: 78%
“…Even though InN has difficulties in synthesis, reports are available on the growth of InN nanorods (NRs) or nanowires (NWs) with different techniques like molecular beam epitaxy (MBE) [4,5], guidedstream thermal chemical vapor deposition (CVD) [11], controlledcarbonitridation reaction route [12], and thermal CVD [13][14][15]. Among these techniques CVD is a commercially viable technique for controlled and large scale synthesis.…”
Section: Introductionmentioning
confidence: 99%